تقليل الإنبعاثات الكبريتية عبر محاكاة Aspen HYSYS V 8.0: بإنشاء مصنع لإنتاج حامض الكبريتيك من الكبريت الصلب الناتج عن معالجة الغاز الطبيعي في مجمع مليتة الصناعي.(دراسة بيئية وتصميم اقتصادي) (Comprehensive Journal of Science, 2025)
The primary objective of this study is to reduce emissions and convert the secondary by-product—namely, elemental sulfur generated from the natural gas sweetening process at the Mellitah plant—into a valuable and economically beneficial product, sulfuric acid. This study addresses the environmental and technical aspects related to assessing the feasibility of establishing an integrated sulfuric acid production plant in Mellitah, with a design capacity of 60 tons per day, employing the single-contact process to produce acid with a purity of 98.5 wt.%. The proposed plant was simulated under steady-state conditions using Aspen HYSYS V8.0 at the designated design capacity. The plant model comprises several operational units, including a dryer, furnace, catalytic converter (four-bed converter), heat exchangers, mixing tank, separators, and a reactive absorption tower. The design and technical specifications of the plant were developed in accordance with specialized industrial and scientific references.The results indicate that the daily sulfur production rate at the Mellitah plant significantly exceeds 19.28 tons/day, reaching an average of 407.67 tons/day in 2024. This quantity is economically sufficient to support a sulfuric acid production capacity of 60 tons/day. A simulation model for a sulfuric acid plant operating via the single-contact system was carried out. Specified material and energy streams were utilized to design the operational units and achieve the maximum possible sulfur dioxide oxidation, which reached 99.4 mol%. Equipment design specifications were calculated based on mathematical correlations established in the sulfuric acid industry. The amount of sulfur dioxide emitted from the proposed plant, as obtained from the simulation model, was approximately 3.767 kg/ton of produced sulfuric acid (around 600 ppm), a value that falls within the acceptable limits established by the U.S. Environmental Protection Agency. Furthermore, the dispersion study of SO₂ emissions from the proposed sulfuric acid plant using Disper V4.0 indicated that concentrations are low and do not affect ambient air quality in the surrounding area. Therefore, constructing this plant at the proposed site (Mellitah) would not pose any health risks to environmental or ecological components.Overall, the establishment of a sulfuric acid production plant represents an environmentally friendly project that ensures the safe and economically viable disposal of elemental sulfur—the by-product of natural gas sweetening—making it an attractive investment opportunity for both the public and private sectors.